iSchools movement science maps - Pérez, Liliana González; Peralta-González, Maria Josefa; Placeres, Grizly Meneses (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. The iSchools Movement is an academic network that studies the interaction of people, technologies and information. The study aims to represent the scientific production of the schools of the iSchools Movement. Design/Methodology/Approach. The research is descriptive with a quantitative approach, it uses as method and fundamental techniques: bibliometric, social network analysis and clúster analysis. A stratified probabilistic sample was formed with 73 member universities from the North American, European and Asian regions in the period 2005-2019. The scientific production was obtained from the Web of Science (WoS), a total of 19,986 records that make up the selected sample were processed. 10 univariate indicators and multivariate representations were calculated from the variables: publications, authors, citations, journals, countries, keywords and themes. Results/Discussion. The intellectual structure from the co-citation of journals and the impact of iSchools point to other areas of knowledge more focused on computational sciences. In Europe, publishing habits and collaboration behavior are expressed within the continent itself, while in North America and Asia greater interrelationships are evident. Conclusions. The consolidation of the iSchools is reaffirmed; It is not only given by the incorporation of new iSchools, but also by the strength of its research. It promotes study and scientific collaboration in the information field and has an impact on other fields of knowledge: computational sciences, interdisciplinary applications and software, information systems, artificial intelligence, management and administration, health sciences and of education.